Pengaruh Penerapan Corporate Social Responsibility Terhadap Citra Perusahaan PT Hadji Kalla Cabang Sultan Alauddin Makassar - Muhtazib Muhtazib; Bintang Balele (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the influence either together or partially between CSR (Corporate Social Responsibility) to corporate image in PT. Hadji Kalla Cabang Sultan Alaudin, Makassar area, that being measured from CSR variables which is Profit, People, and Planet. Expectedly the information obtained from this research can be used by companies to increase CSR activities and quality of CSR programs so that more can enhance the company image in the future. This study uses quantitative methods with explanatory research type with primary and secondary data. Population in this study is the customer PT. Hadji Kalla Cabang Sultan Alauddin, in Makassar and from the population the researcher take 100 adult people as research sample. As for the data analysis technique the researcher uses linear multiple regression and partial with SPSS 17 software. The result of this study found that variables within CSR concept which is Profit (Xi), People (X2), Planet (X3) simultaneously have a significant influence to the corporate image (Y). People (X2) became the most dominant variables that influence the corporate image with regression coefficient values 0,342.